Critical Pedagogy Implementation in Science Education as Perceived by Science Educators - Makiaway, Jaydione; Raganas, Shaina Ella; Serbo, Divine Nicole; Diquito, Tomas JR (Balai Publikasi Indonesia, 2025)
Critical pedagogy (CP) is a crucial instructional approach that aims to increase students' knowledge while fostering a greater awareness of justice and social equality. This approach is used in different disciplines to foster meaningful learning. In science education, CP is used by educators to deepen conceptual learnings by allowing learners to think the social implications of the concept being learned. Thus, this study is created to assess science educators' understanding of CP in basic science education, considering their length of service and gender. The used of quantitative research design is employed to accomplish the objectives of the study. In addition, respondents were drawn using simple random sampling technique and curated with the inclusion criteria. Based on this, 109 science educators across the province of Davao del Sur, Philippines were randomly selected as respondents to the study. The use of mean, standard deviation, Mann-Whitney U-Test, and Kruskal-Wallis H Test were used to analyze the data. The findings of the study revealed that science educators have an overall high level of understanding of CP with a very high level in the indicator, program structure. Moreover, data shows a moderate level of understanding in the indicators evaluation and teacher development. The analysis further revealed that gender does not play a significant role in understanding CP. However, when analyzed by length of service, data shows a statistically significant difference in the overall CP along with the indicators of philosophical orientation and teacher-student relationship. The findings of the study imply that science educators should be empowered to integrate CP in the classroom and implement professional development programs to improve CP understanding, especially for newly employed science educators